1999
DOI: 10.1128/aem.65.12.5293-5302.1999
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection, Characterization, and Distribution of Virulence Genes in Aeromonas spp

Abstract: We found 73.1 to 96.9% similarity by aligning the cytolytic enterotoxin gene of Aeromonas hydrophila SSU (AHCYTOEN; GenBank accession no. M84709 ) against aerolysin genes ofAeromonas spp., suggesting the possibility of selecting common primers. Identities of 90 to 100% were found among the eight selected primers from those genes. Amplicons obtained fromAeromonas sp. reference strains by using specific primers for each gene or a cocktail of primers were 232 bp long. Of hybridization group 4/5A/5B (HG4/5A/5B), H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
3
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(84 citation statements)
references
References 47 publications
7
71
3
3
Order By: Relevance
“…Our study demonstrated that the occurrence of the aerolysin/hemolysin genes in A. popo¤i (92%) is similar to that in common clinical species (e.g. A. veronii bt sobria), and also in the ¢sh pathogen A. salmonicida [13]. In the original description, the isolates of A. popo¤i were tested in sheep blood at 37³C and considered non-L-hemolytic [3].…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Our study demonstrated that the occurrence of the aerolysin/hemolysin genes in A. popo¤i (92%) is similar to that in common clinical species (e.g. A. veronii bt sobria), and also in the ¢sh pathogen A. salmonicida [13]. In the original description, the isolates of A. popo¤i were tested in sheep blood at 37³C and considered non-L-hemolytic [3].…”
Section: Resultsmentioning
confidence: 64%
“…Sequences from GenBank (GB) and European Molecular Biology Laboratory (EMBL) were used to design primers (Primer Designer 3 software, Scienti¢c Educational Software, Durham, NC, USA) for each group of genes ( Table 2) after alignment with a CLUSTAL W program [12]. The gene accession numbers for aerolysin/hemolysin were those of the 10 sequences used by Kingombe et al [13], while the others were: serine protease, GB AF159142 [14] and EMBL X67043 [15]; GCAT, EMBL X70686 [16] and X07279 [17]; lipases, GB U63543 [18], S65123 [19], AF092033 [20] and U14011 [21]; DNase, GB AF004392 (unpublished), L78266 [22] and M99491 [23]. PCR ampli-¢cations were performed with 1.2^2 Wg of DNA as previously described [11] and using conditions shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The genes that encode the flagella (fla), lateral flagella (lafA), elastase (ahpB), cytotoxic and cytotonic enterotoxins (act, ast, alt), lipase (pla/lipH3/apl-l/lip), aerolysin/haemolysin (aerA) and serine protease (serine) were screened for all strains of both species using the conditions and primers described previously (Kingombe et al, 1999;Chacó n et al, 2004;Sen & Rodgers, 2004;Aguilera-Arreola et al, 2005). The TTSS genes ascF-G and ascV and the genes encoding the toxins delivered by this system, that is, AexT (aexT) and AopP (aopP), were investigated using conditions and primers previously described (Braun et al, 2002;Chacó n et al, 2004;Fehr et al, 2006).…”
Section: Detection Of Putative Virulent Genesmentioning
confidence: 99%
“…An interesting approach for the direct detection of potentially pathogenic Aeromonas spp. isolates is the use of virulence determinants as genetic markers (Kingombe et al 1999).Analysis of pathogenic mechanisms associated with A. hydrophila has identified various virulence factors including toxins with haemolytic, cytotoxic and enterotoxic activities Singh et al 2009), protease (Cascó n et al 2000a,b), and structural features associated with adhesion, cell invasion and resistance to phagocytosis, such as S-layer proteins (Murray et al 1988). Heuzenroeder et al (1999) reported that the direct detection of the haemolytic genes aerA and hlyA was a reliable approach for identifying potentially pathogenic Aeromonas strains.…”
mentioning
confidence: 99%